Negotiation of Santri Agency in the Practice of Munaqosyah Tilawah: A Case Study at Ma'had Dhiyau'l Quran Negotiating Santri Agency in Quranic Recitation Assessments: A Pedagogical Case Study in an Islamic Boarding School - Muhammad Qomaruddin; Moh Ali; Nuryana; Fujianti (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2026)
This study aims to analyze how the agency of students is negotiated—defined as the capacity of students to navigate and exert influence within structured educational environments—in the practice of Munaqosyah Tilawah (a formal oral examination of Quranic recitation skills) at Ma'had Dhiyau'l Quran. A qualitative approach with a case study design was employed, purposively involving 6 students and 3 ustaz to obtain in-depth experiential data from a specialized cohort. Data were collected through interviews, observations, and documentation, then analyzed using thematic analysis by systematically coding field notes and transcripts to identify recurring patterns of student agency. The analysis focused on the dynamics of students' experiences in a public, structured evaluative forum. The results of the study indicate that the negotiation of agency takes place through four main fields: (1) an emotional threshold where students navigate nervousness and anxiety as an initial mental test; (2) relationship-based agency where performance is influenced by parental and teacher encouragement as a form of socio-religious accountability; (3) bodily limitations in tilawah (recitation) performance, especially breath regulation and tone control; and (4) self-reflexivity that raises awareness of abilities and targets for improvement. Munaqosyah not only serves as a technical evaluation of reading but also as a pedagogical space that shapes religious subjects through the interaction among emotional pressure, social relations, physical discipline, and spiritual orientation. This study contributes to Islamic education research by illustrating how evaluative practices can become sites of personal empowerment. Practically, munaqosyah should be designed supportively to foster sustainable student agency.